2010
DOI: 10.1111/j.1439-0310.2010.01769.x
|View full text |Cite
|
Sign up to set email alerts
|

What Makes Vocalisation Frequency an Unreliable Signal of Body Size in Birds? A Study on Black Swans

Abstract: In many animal species, the frequency (pitch) of vocalisations correlates negatively with body size and may thus signal competitive ability. However, this relationship is absent in other species. Understanding why this difference exists across species may help to explain some of the diversity of vocal communication systems. We assessed whether vocalisation frequency signals body size in black swans (Cygnus atratus), and how this is affected by (i) variation in frequency within individuals and (ii) size variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 53 publications
1
40
1
Order By: Relevance
“…However, fundamental frequency rarely correlates with size in mammals [10], instead formant dispersion more commonly indicates size [11], [12]. For the complex vocalisations of songbirds, empirical support is rare (reviewed in [13], [14]) despite detailed study [15], and limited to a single example: larger male barn swallows sing the rattle syllable of their songs at lower frequencies [16]. Other studies have demonstrated frequency variation associated with size differences between populations [17], [18], likely due to population differences in habitat or selection pressures [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, fundamental frequency rarely correlates with size in mammals [10], instead formant dispersion more commonly indicates size [11], [12]. For the complex vocalisations of songbirds, empirical support is rare (reviewed in [13], [14]) despite detailed study [15], and limited to a single example: larger male barn swallows sing the rattle syllable of their songs at lower frequencies [16]. Other studies have demonstrated frequency variation associated with size differences between populations [17], [18], likely due to population differences in habitat or selection pressures [18].…”
Section: Introductionmentioning
confidence: 99%
“…Since frequency ranges are usually larger than those expected due to within-sex variation in size, this vocal complexity could obscure a relationship between body size and frequency [13], [14]. However, theory predicts that body size limits the production of loud, low-frequency sounds [3], so it is only the lower limit of the full frequency range that should be constrained by size.…”
Section: Introductionmentioning
confidence: 99%
“…In both of these studies, the inclusion of species exhibiting a wide range of body sizes (~5–1400 g in10 and 14–155 mm in11) appears to have been critical. Studies examining narrower ranges of body sizes, e.g., within a single species, have produced mixed results, finding evidence for negative allometry in some cases121314 but not others15161718.…”
mentioning
confidence: 99%
“…It is important to note that while many studies have found a relationship between fundamental frequency and body size in several species (e.g., Bowling et al, 2017;Charlton & Reby, 2016;Gingras, Boeckle, Herbst, & Fitch, 2013;Hauser, 1993;Wallschläger, 1980), others have not (e.g., Patel, Mulder, & Cardoso, 2010;Rendall, Kollias, Ney, & Lloyd, 2005;Sullivan, 1984). As noted by Bowling et al (2017), a relevant factor seems to be the range in body sizes 16 The authors theorize that two separate, but potentially related, processes may be at work.…”
mentioning
confidence: 99%